2005
DOI: 10.1029/2005gl024079
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐year integrated atmospheric water vapor record using precision filter radiometers at two high‐alpine sites

Abstract: [1] Measurements of integrated water vapor (IWV) density using precision filter radiometers (PFRs) at two high-alpine, mid-latitude stations in the Swiss Alps are reported. ) and a large negative bias at JFJ (À1.5 kg m À2 ). Microwave radiometer IWV at JFJ agreed well with PFR IWV suggesting that GPS IWV suffers from unmodeled effects. Linear IWV trend analysis indicated no significant trend at either Davos or JFJ for clear-sky periods. The GPS-IWV time series is at present too short to determine the trend for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 13 publications
3
23
1
Order By: Relevance
“…This introduces a negative fair weather bias in the IWV data, since cloudy conditions are often associated with higher IWV values. Nyeki et al (2005) found a small dry bias of 0.4 mm of a precision filter radiometer (sun photometer) with respect to a GPS receiver at Davos in Switzerland.…”
Section: Sun Photometermentioning
confidence: 99%
“…This introduces a negative fair weather bias in the IWV data, since cloudy conditions are often associated with higher IWV values. Nyeki et al (2005) found a small dry bias of 0.4 mm of a precision filter radiometer (sun photometer) with respect to a GPS receiver at Davos in Switzerland.…”
Section: Sun Photometermentioning
confidence: 99%
“…Measurements are made in sunny conditions at time intervals of between 30 s and 2 min (depending on the station), and are averaged over hourly periods before being stored in the database. Continuous sun photometer measurements began at Davos in 1995 (Nyeki et al, 2005), at Jungfraujoch in 1999, at Locarno in 2001 and at Payerne in 2002. Since the CHARM network also measures global solar irradiance and infrared (long-wave) irradiance from the atmosphere, it provides the opportunity for linking IWV observations to changes in atmospheric radiation.…”
Section: Sun Photometer/precision Filter Radiometer Measurementsmentioning
confidence: 99%
“…Finally, the relatively low cost and easy deployment of sun photometers allowed the establishment of several international networks in the last 30 years worldwide. AErosol RObotic NETwork (AERONET) network (Holben et al, 1998;Smirnov et al, 2004), Global Atmospheric Watching Precision Filter Radiometer (GAW-PFR) network (Wehrli, 2000;Nyeki et al, 2005) and European Skynet Radiometers (ESR-SKYNET) network (Campanelli et al, 2012(Campanelli et al, , 2014 provide operationally free estimation of W or develop algorithms and open-source packages for improving the retrieval of this important atmospheric pa- rameter. However, the great problem of this methodology is the estimation of the sun-photometric calibration parameters.…”
mentioning
confidence: 99%